Toll-like Receptors: Key Players in Antiviral Immunity - Arpaia, Nicholas (2011)
TLRs are a family of innate receptors whose specificities are predetermined in the germline. Therefore, TLRs have evolved to recognize conserved features of microbes. Viruses typically lack the conserved features common to other pathogen classes, so the innate immune system has evolved to recognize viral nucleic acid as a hallmark of viral infection. In this review we discuss examples of TLR-mediated viral recognition and the functional consequences of this recognition for antiviral immunity.